International responsibility of the Peruvian State referred to the judgments of the Inter-American Court of Human Rights - Reyes Menéndez, Valeria (Derecho & Sociedad, 2017)
This event revolves around some relevant aspects regarding the responsibility of the State at the international level, such as the effectiveness of the judgments of the Inter-American Court of Human Rights and the position of Peru in this international entity.